Efektivitas fitoremidiasi kayu apu (Pistia stratiotes) dan eceng gondok (Eichhornia crassipes) dalam memenuhi baku mutu air limbah di instalasi pengolahan air limbah RSUD Kabupaten Badung Mangusada - I Kadek Prastikanala; I Made Wahyu Wijaya (Bioculture Journal, 2023)
Hospital liquid waste can be infectious, poisonous and harmful for hospital environment and communities surrounding. The examination result of liquid waste outlet in Mangusada hospital within January - August 2016 showed an increase in free Ammonia (NH3) quality raw at the level of 3.71 mg / L and phosphate (PO 4) up at the level to 3.38 mg / L. To anticipate the pollution of liquid waste which might occur, liquid waste treatment is an absolute option to be required. The objective of this research is to obtain the effectiveness of kayu apu and hyacinth in complying liquid waste quality standard. This research is quasi experiment using non-equivalent control group design with post test. The conclusion of this research showed that liquid waste management system refers to environmental health hospital requirements and it licensed on disposal of water resources and reuse of liquid waste environmental Board of Badung Regency. The results of an independent analysis showed that kayu apu phytoremediation is more (p <0.05) in complying the quality standard especially on the indicator of liquid waste mainly on NH3 and COD. Kayu apu lettuce can be apply as an alternative option in complying quality standard of liquid waste using biology system.